Integration of Basic and Clinical Sciences: Faculty Perspectives at a U.S. Dental School. - van der Hoeven, Dharini; van der Hoeven, Ransome; Liang Zhu; Busaidy, Kamal; Quock, Ryan L.; Zhu, Liang (Journal of Dental Education, 2018)
Although dental education has traditionally been organized into basic sciences education (first and second years) and clinical education (third and fourth years), there has been growing interest in ways to better integrate the two to more effectively educate students and prepare them for practice. Since 2012, The University of Texas School of Dentistry at Houston (UTSD) has made it a priority to improve integration of basic and clinical sciences, with a focus to this point on integrating the basic sciences. The aim of this study was to determine the perspectives of basic and clinical science faculty members regarding basic and clinical sciences integration and the degree of integration currently occurring. In October 2016, all 227 faculty members (15 basic scientists and 212 clinicians) were invited to participate in an online survey. Of the 212 clinicians, 84 completed the clinician educator survey (response rate 40%). All 15 basic scientists completed the basic science educator survey (response rate 100%). The majority of basic and clinical respondents affirmed the value of integration (93.3%, 97.6%, respectively) and reported regular integration in their teaching (80%, 86.9%). There were no significant differences between basic scientists and clinicians on perceived importance (p=0.457) and comfort with integration (p=0.240), but the basic scientists were more likely to integrate (p=0.039) and collaborate (p=0.021) than the clinicians. There were no significant differences between generalist and specialist clinicians on importance (p=0.474) and degree (p=0.972) of integration in teaching and intent to collaborate (p=0.864), but the specialists reported feeling more comfortable presenting basic science information (p=0.033). Protected faculty time for collaborative efforts and a repository of integrated basic science and clinical examples for use in teaching and faculty development were recommended to improve integration. Although questions might be raised about the respondents' definition of "integration," this study provides a baseline assessment of perceptions at a dental school that is placing a priority on integration.